A Review on Effectiveness of Numerous Technologies by Utilizing Hydrogen - Mohd Syafiq, Sharip; Norazlianie, Sazali; Haziqatulhanis, Ibrahim; Ahmad Shahir, Jamaludin (SpringerLink, 2019)
Numerous technologies for H2-rich gaseous mixture production has been know through studies. However, most approaches do not satisfy the purity level for certain process such as fuel cell technology that demands a high-purity hydrogen supply (>99.99 vol.%). Therefore, purification technology to purify hydrogen is taken into consideration in order to meet purity requirement by certain applications, and it is a key factor to efficient hydrogen supply. In addition, CO2 capture in pre-combustion of integrated gasification combined cycle (IGCC) power plants include the separation of H2-CO2 to generate electricity at a lower hydrogen purity. Advantage of hydrogen gaseous are its low volumetric energy density compared to other materials and the storage is essential for wider applications using hydrogen as well as hydrogen purification.